Landscape architecture as a perspective of energy and recourses conservation - Aldeberky, Amal Abdal-haleem (2008)

(untitled)
The paper presents the effect of urban planted area in conserving the energy consumption and recourses conservation. An analytical study reviews the local urban landscape features prevailed during the ancient Egyptian, Greek and Roman culture, and flourished in Islamic civilization; also, the paper examines the key features of modern urban landscape design practices which are compatible with climate, social, economic and environmental issues, Case studies from hot desert regions such as Egypt, Arizona and Nakab that revives the Islamic theories for urban landscape, resources conservation and sustainability. Moreover, the paper also reviews the field studies to measure the effect of green areas in modifying the urban climate, in order to deduce the criteria of distribution of green areas through housing and public projects in respect of energy and recourse conservation.